Dielectric properties, electric modulus and conductivity profiles of Al/Al2O3/p-Si type MOS capacitor in large frequency and bias interval - Turk, Cagri Gokhan; Altindal, Şemsetti̇n; Tan, Serhat Orkun; Çi̇çek, Osman (Elsevier BV, 2022)
The letter reports that the impedance spectroscopy method has been performed to acquire impeccable results on the ac electric conductivity (σac), dielectric (ε′ and ε′′) and electric modulus (M' and M'') components of the Al/Al2O3/p-Si type MOS capacitor. The relevant parameters are defined with C-V-f and G/ω-V-f data between 1 kHz and 5 MHz and ± 3 V at room temperature. Both parts of dielectric constants are decreasing at high frequencies to prevent the interface dipoles from gaining enough time to return to the alternative area. Depending on the restructuring and reorganization of surface states (Nss) in the alternative field, tanδ decreases at higher frequencies. The M' values reach maximum by frequency increment in the depletion region, while M'' values shift to the forward biases depending on a certain density distribution of Nss. The σac values increase with increasing frequency in the accumulation region depending on series resistance. Considering polarization processes, surface conditions (Nss) and Al2O3 interlayer, frequency and biases are extremely effective and dependent on the dielectric specifications, electrical modulus and conductivity.
Keywords: Frequency dependence; Conductivity; Electric modulus; Surface states; Dielectric properties; Polarization; TA1-2040; Engineering (General). Civil engineering (General)